Low Consumption of Indigenous Fresh Dairy Products in Ghana Attributed to Poor Hygienic Quality - Parry-Hanson Kunadu, A.; Aboagye, E.F.; Colecraft, E.K.; Otoo, G.E.; Adjei, M.Y.B.; Acquaah, E.; Afrifa-Anane, E.; Amissah, J.G.N. (Journal of Food Protection, 2019)
This cross-sectional study was aimed at assessing consumer perceptions and microbiological quality of the fresh cow's milk products available in selected dairying communities in Ghana. Twenty-six focus groups (FGs) were conducted to understand the perceptions on barriers and facilitators to dairy consumption. These included six FGs for lactating mothers and five FGs for each of the following categories: pregnant women, women of reproductive age with children younger than 5 years, not pregnant and nonlactating women, and males. A separate quantitative survey followed and included 176 women of reproductive age (18 to 49 years) and 90 males (18 to 59 years) from 15 dairying communities in the Greater Accra, Eastern, and Central regions of Ghana. Also, 120 locally sourced fresh milk products were assessed for counts of total coliforms, fecal coliforms, and Enterococcus spp., and presence of pathogenic Streptococcus spp. , Escherichia coli, and Klebsiella pneumoniae by using standard microbiological methods. Fecal coliforms in dairy products, such as brukina, wagashi, and yogurt exceeded the specified limit of 10 CFU/mL, while the prevalence of E. coli and K. pneumoniae were 70 and 65%, respectively. Generally, respondents perceived indigenous dairy as unsafe. These perceptions were formed on the basis of visual cues of environmental and personal hygiene. Of the indigenous milk products consumed, brukina, a fermented milk and millet gruel (33%) and wagashie, a soft unfermented cheese (29%), were the most popular. However, only 19% of wagashie and 21% of brukina consumers believed these products were safe. Consistently, the odds of consuming a particular milk product was significantly higher if the consumer believed it was safe. Poor sanitation and unhygienic processing of otherwise healthy but perishable indigenous milk products has justifiably fueled the mistrust of consumers and may hinder potential intervention efforts to increase milk production and consumption in Ghana.
Keywords: Consumer perceptions; Dairy products; Microbial contamination; Milk